Comparative Analysis of Bioelectrocatalytic Cytochrome P450 3A4 Systems - Koroleva, P.I.; Shumyantseva, V.V. (Biomedical Chemistry: Research and Methods, 2024)
This article describes the approaches developed by the authors with the aim to increase the efficiency of electro enzymatic reactions catalyzed by cytochrome P450 3A4. A comparative analysis of cytochrome P450 3A4 systems was carried out during the formation of the functional complexes hemoprotein-flavin nucleotides as low-molecular models of NAD(P)H-dependent cytochrome P450 reductase. The formation of a productive enzyme-substrate complex before the stage ofaccepting electrons from the modified electrode was studied from the electocatalytic viewpoint. Incorporation of the enzyme into nanopores of different nature on the electrode (2D-3D transition) was also studied. The results on the electrochemical reduction of bactosomes as the functionally active models of the microsomal monooxygenase system are also considered. The electrochemical and electrocatalytic parameters of cytochrome P450 3A4 were compared for different models of the electrocatalytic generation of metabolites.